2020
DOI: 10.1088/1755-1315/446/3/032017
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and thermodynamic analysis of adsorption of naproxen by activated sludge

Abstract: Naproxen, a new environmental drug pollutant, shows “false persistence” in the environment and causes certain risks to human health and ecological environment, which has attracted extensive attention. The activated sludge in the sewage treatment technology plays a significant role in the control of the naproxen content. This paper carried out the kinetics and thermodynamic analysis of the adsorption process of naproxen by activated sludge. The experimental results show that the adsorption process of naproxen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Recently, the role of activated sludge in the adsorption of organic pollutants has received extensive attention. For instance, Prado et al 9 found that activated sludge has a good adsorption effect on tetracyclines, and the study of Tang et al 10 showed that activated sludge has a good adsorption effect on naproxen organic matter. The adsorption of reactive dyes on sludge surfaces is classified as monolayer adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the role of activated sludge in the adsorption of organic pollutants has received extensive attention. For instance, Prado et al 9 found that activated sludge has a good adsorption effect on tetracyclines, and the study of Tang et al 10 showed that activated sludge has a good adsorption effect on naproxen organic matter. The adsorption of reactive dyes on sludge surfaces is classified as monolayer adsorption.…”
Section: Introductionmentioning
confidence: 99%